The Issuance Of A Business Identification Number (NIB) As A Step Toward Legalization And Halal Certification Of MSME Products Of Naru Snack In Jambi City - Sudharyati, Neneng; Anggraini, Dessy; Wulandari, Ayu; Umariah, Riska; Hartati, Fitriyanti; Putri Br Ginting, Loisa; Firmansyah Chandra, Rizky (Fakultas Ekonomi dan Bisnis Islam - IAIN Lhokseumawe, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in supporting economic growth in Indonesia. However, many MSMEs lack business legality and halal certification, including Naru Snack in Jambi City. This study aims to assist MSMEs in obtaining a Business Identification Number (NIB) and halal certification, ensuring legitimate business legality and strengthening consumer trust in their products. The method used is descriptive qualitative, using observation, interviews, and documentation. The mentoring process was conducted through the Online Single Submission (OSS) system for NIB registration and the SiHalal system for halal certification applications. The results of this activity indicate that this mentoring was successful in helping partners obtain NIBs and register for halal certification. With this legality, Naru Snack can increase its competitiveness and expand its market reach. This activity also raises awareness among MSMEs about the importance of legality and compliance with applicable laws and regulations.